INFORMATIONAL ECONOMY AND INFORMATIONAL SOCIETY - A. M. Tufetulov (Russian Journal of Economics and Law)
The article deals with the problems of formation of informational economy and informational society. It presents the theoretical analysis of notional apparatus and basic features of informational economy which make it different from other economical models.